Graphene and its sensor-based applications: A review - Nag, Anindya; Mitra, Arkadeep; Mukhopadhyay, Subhas Chandra (Sensors and actuators. A. Physical., 2018)
•Review on the fundamentals of graphene: preparation, properties and application.•The preparation procedure Chemical Vapor Deposition, Mechanical Exfoliation and Hummer’s method.•The applications include sensors with electrodes having graphene in its pure and nanocomposite form.•Three types of applications namely electrochemical, strain and electrical sensors are explained, based on the operating principle of the sensors.•The strength, limitations of the current graphene sensors along with their future opportunities. This paper presents an overview of the work done on graphene in recent years. It explains the preparation techniques, the properties of graphene related to its physio-chemical structure and some key applications. Graphene, due to its outstanding electrical, mechanical and thermal properties, has been one of the most popular choices to develop the electrodes of a sensor. It has been used in different forms including nanoparticle and oxide forms. Along with the preparation and properties of graphene, the categorization of the applications has been done based on the type of sensors. Comparisons between different research studies for each type have been made to highlight their performances. The challenges faced by the current graphene-based sensors along with some of the probable solutions and their future opportunities are also briefly explained in this paper.